Mitochondrial dysfunction fuels drug resistance in adult T-cell acute lymphoblastic leukemia - Guo, Shanshan; Bourova-Flin, Ekaterina; Rousseaux, Sophie; Chuffart, Florent; Peng, Lijun; Jing, Duohui; Mi, Jian-Qing; Khochbin, Saadi; Wang, Jin (Journal of translational medicine, 2025)
T-cell acute lymphoblastic leukemia (T-ALL) is a relatively rare hematological malignancy, characterized by the uncontrolled proliferation of immature T lymphoblasts and associated with a generally unfavorable prognosis. Our previous research has demonstrated that decreased mitochondrial activity is associated with the aggressiveness of T-ALL tumors. However, the mechanisms underlying this phenomenon and its contribution to treatment resistance remain largely elusive. We have built up the largest known T-ALL tumor bank, with a median follow-up of 32 months, including our transcriptomic data from 79 newly sequenced tumors that adds to the 54 publicly accessible samples. Computational analyses and a series of functional assays were performed to investigate the molecular links between altered mitochondrial activity and drug resistance. The transcriptomic analysis revealed that down-regulation of mitochondrial activity is a potent driver of ABCB1 activation, a gene strongly associated with multidrug resistance. In tumors with low mitochondrial activity, the impaired fatty acids β-oxidation leads to intracellular lipid accumulation, which is directly involved in ABCB1 activation. Indeed, our data show that lipid neo-synthesis and accumulation promotes the activation of lipogenic transcription factors, liver X receptors (LXRs), which act as drivers of ABCB1 expression. Tumor data analyses confirmed that high ABCB1 expression in tumour samples is indeed associated with reduced mitochondrial gene expression, lipid droplet enrichment, increased tumour aggressiveness, and significantly shorter patient survival. Our study demonstrates that reduced mitochondrial activity drives multidrug resistance in adult T-ALL via lipid-mediated activation of ABCB1. These findings enhance our understanding of the biology of aggressive T-ALL and provide insight into mechanisms of resistance to conventional chemotherapy. Consequently, we propose that targeting de novo lipogenesis and restricting dietary fats, such as caprylic acid, may help overcome treatment resistance in patients with T-ALL exhibiting low mitochondrial activity. The clinical trial was registered under the identifiers ChiCTR-ONRC-14004968 and ChiCTR2000031553 at ClinicalTrials.gov.